El rótulo comercial. Protagonista de nuestra realidad - Jonay Cogollos van der Linden (Eme, 2013)
Street signs are the media for advertising in our closest urban environment. They are intended to indicate information that is not outwardly observable in complex built-up landscapes. Commercial graphics puts its stamp on the urban environment. This study therefore enables us to better understand reality, culture and, ultimately, the world around us.